Fetal Growth Restriction: A Pragmatic Approach - Nadel, Allan; Prabhu, Malavika; Kaimal, Anjali (American Journal of Perinatology, 2024)
An accurate diagnosis of fetal growth restriction relies on a precise estimation of gestational age based on a carefully obtained history as well as early ultrasound, since a difference of just a few days can lead to a significant error. There is a continuum of risk for adverse outcome that depends on the certainty of dates and presence or absence of comorbidities, in addition to the estimated fetal weight percentile and the umbilical artery waveform. The results of several studies, most notably the TRUFFLE trial, demonstrate that optimal management of fetal growth restriction with an abnormal umbilical artery waveform requires daily electronic fetal heart rate monitoring, and this monitoring does not require computerized interpretation. The role of ductus venosus waveform, biophysical profile, and middle cerebral artery waveform is less clear, and the results of these three modalities should be interpreted with caution.
Keywords: fetal growth restriction; ductus venosus waveform; feta heart rate monitoring; biophysical profile; middle cerebral artery waveform